2008
DOI: 10.2174/187231208785425818
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Oxidase Activity and Inhibition in Hepatocytes and Cytosolic Fraction from Mouse, Rat,Monkey and Human

Abstract: Aldehyde oxidase (AO) is a cytosolic enzyme that contributes to the Phase I metabolism of xenobiotics in human and preclinical species. We compared AO activity in cytosol and cryopreserved hepatocytes from human, monkey, rat and mouse livers to assess species differences. We also evaluated possible species differences in drug interactions using seven drugs known to inhibit human cytosolic AO i.e. raloxifene, perphenazine, menadione, maprotiline, ketoconazole, erythromycin, and estradiol. AO activity was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 0 publications
6
36
0
Order By: Relevance
“…Despite the fact that our overall results were in agreement with species difference of AO catalytic activity reported in the literature (Kitamura et al, 2006;Sahi et al, 2008;Pryde et al, 2010), more robust AO activity oxidizing 5BPO and related oxazoles was observed in mouse liver cytosol over monkey or human liver cytosol. This could possibly be an oxazole-chemotype-specific or compound-specific phenomenon.…”
Section: Downloaded Fromsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite the fact that our overall results were in agreement with species difference of AO catalytic activity reported in the literature (Kitamura et al, 2006;Sahi et al, 2008;Pryde et al, 2010), more robust AO activity oxidizing 5BPO and related oxazoles was observed in mouse liver cytosol over monkey or human liver cytosol. This could possibly be an oxazole-chemotype-specific or compound-specific phenomenon.…”
Section: Downloaded Fromsupporting
confidence: 90%
“…Likewise, metabolite resulting from oxidation of zoniporide by AO in the quinoline ring was a primary metabolite in humans and rats but was not observed in dogs . On the other hand, zebularine was found to be metabolized by AO with higher V max observed in mouse than in human and monkey liver cytosols (Klecker et al, 2006), and the order of AO activity, measured by the rate of vanillic acid formation from vanillin, was monkey Ͼ mouse Ͼ human Ͼ rat liver cytosol, with no activity seen in dog cytosol (Sahi et al, 2008). When 5BPO was incubated in liver cytosols from various species including the rat, mouse, dog, monkey, and human (Table 3), maximal turnover of 5BPO was observed in mouse liver cytosol (t 1/2 ϭ 7 min) followed by monkey liver cytosol (217 min).…”
Section: Downloaded Frommentioning
confidence: 96%
“…SKF525-A, a reported inhibitor of AO, did not inhibit the formation of this metabolite in monkey cytosol (95% of control), whereas M11 formation was inhibited by SKF525-A in human cytosol (62% of control). It should be noted that inhibition of molybdenum hydroxylases is less understood than is the case with P450s, and the same AO inhibitor can exhibit different inhibitory potentials among species and for different marker substrates (Sahi et al, 2008). Together, these data suggested that AO and not XO is the enzyme responsible for the formation of the M11 metabolite in the monkey and human.…”
Section: Resultsmentioning
confidence: 99%
“…A panel of widely used AO inhibitors with different chemical structures and properties, including raloxifene (Obach, 2004), DCPIP (Barr and Jones, 2011), menadione (Johns, 1967;Sahi et al, 2008;Barr and Jones, 2011), and b-estradiol (Johns et al, 1969;Barr and Jones, 2011), inhibited GDC-0834 metabolism (formation of M1) with low single-digit micromolar IC 50 values (Table 1). There was also evidence for CES-mediated amide hydrolysis in HLC (and DLC and human blood and plasma; see discussion to follow).…”
Section: Discussionmentioning
confidence: 99%